The European Commission in the 21st century: core beliefs on EU governance - Hooghe, Liesbet (2012)
Abstract: What lives in the European Commission at the beginning of the 21st Century? This paper charts Commission officials’ views on the governance, ideological direction, and policy scope of the European Union, employing data from a large survey conducted in Autumn 2008. First, the Commission is not a hothouse for supranationalism. True, supporters of a supranational Union with the College of Commissioners as the government of Europe and member states in the back seat are the largest minority, but they are outnumbered two-to-one by state-centric, pragmatist, and ambivalent officials. There are striking differences in distribution by nationality, gender, and department. Second, where do Commission officials stand on ideology? The answer is that the Commission is broadly representative of European societies, at least on traditional economic left/right issues, though decidedly more socio-liberal. Ideological views are not randomly distributed across services, with social DGs significantly mo